Enhanced removal of Cu(II) and Ni(II) from binary systems by Ca-modified low-temperature pine bark biochar - Eun-Chae Im; Jae-In Lee; Seong-Jik Park; Chang-Gu Lee (Biomass and Bioenergy, 2027)

Bioavailability-based ecological risk assessment of metals in coastal sediments from industrial bays in South Korea: Insights from geochemical fractionation and source identification - In-Gyu Cho; Min-Jae Jo; In-Seok Lee; Sung-Deuk Choi (Marine Pollution Bulletin, 2026)

Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

Correction to: Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)

Diacerein improves liver fibrosis, steatosis, and atherosclerosis in ApoE knockout mice - Jie-Eun Lee; Isom Jin; Jung-Jae Lee; Jisu Jung; Jee-In Lee; Bo-Rahm Kim; Tae Jung Oh; Yun Kyung Lee; Sung Hee Choi (Journal of Molecular Medicine, 2026)
Non-alcoholic fatty liver disease and atherosclerosis may share a common pathogenesis involving chronic IL-1β-induced inflammation. We aimed to evaluate the efficacy of diacerein, an IL-1 pathway inhibitor, in improving liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E-knockout (apoE k/o) mice. ApoE k/o mice fed a high-fat diet (HFD) were divided into three groups based on diacerein dosage. Liver fat accumulation and fibrosis severity were compared across groups, along with changes in the expression of genes related to lipid metabolism and fibrosis. Atherosclerotic burden in the aorta was evaluated via en face analysis, and the related signaling pathway was verified in vitro. Diacerein treatment reduced the amount of collagen fibers and fat accumulation in the liver in a dose-dependent manner as well as fibrosis-related gene expression. Atherosclerotic plaque burden in the aorta showed a decreasing trend with diacerein treatment, accompanied by reduced expression of pro-inflammatory cytokines, including TNF-α. Diacerein treatment ameliorated liver steatosis/fibrosis and showed beneficial effects on atherosclerosis-related mechanisms in HFD-fed apoE k/o mice. Given its dual anti-inflammatory and anti-fibrotic actions, diacerein represents a promising therapeutic candidate for metabolic disorders characterized by chronic inflammation. Key messages We analyzed the effects of diacerein on liver fibrosis, steatosis, and atherosclerosis in apolipoprotein E knockout (apoE k/o) mice. Diacerein reduced fat accumulation in the liver and collagen fibers in the liver. It decreased the expression of genes related to fibrosis and the burden of atherosclerotic plaque in the aorta. The expression of pro-inflammatory cytokines was reduced. Treatment of apoE knockout mice fed an HFD with diacerein effectively ameliorated liver steatosis/fibrosis and atherosclerosis. Graphical Abstract

Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Decoupled storm-phase source dynamics of dissolved and particulate organic matter in an agricultural watershed - Yun Kyung Lee; Ho-Yeon Park; Haeseong Oh; Seung-Hee Kim; Kyung-Hoon Shin; Jae-In Kim; Byung Joon Lee; Jin Hur (Journal of Hydrology, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Microphysiological system-based respiratory toxicity assessment: recent advances and regulatory perspectives - In Jae Bang; Min-Seok Kim; Yubin Han; Ga Eun Kim; Jung Eun Lim; Ji Yeong Park; Jin Yoo; Young Seo Jang; Beomhee Lee; Minjin Kwak; Soojin Park; Wonjun Jang; et al. (Toxicological Research, 2026)

Occupational risk assessment of p-tert-butylphenol: toxicity reference values and worker exposure evaluation - In Jae Bang; Ji Hyun Yu; Jung Eun Lim; Yubin Han; Yerim Koo; Damee Eun; Daeyeop Lee; Ig-Chun Eom; Ha Ryong Kim (Toxicological Research, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Diagnosis classification in EMR data using latent representations and SNOMED-CT mapping for improved medical data integration - Sungsu Oh; In Ho Han; Jae Il Lee; Byung Kwan Choi; Hyunsu Lee (Medical & Biological Engineering & Computing, 2026)

Inkjet-printed full-color tandem quantum dot light-emitting diode with dual-color subpixels - Young-Jae Ko; Gyu-jin Shin; Hyo-Bin Kim; Seung-Ah Lee; Jae-In Yoo; Jun Hyup Lee; Jang-Kun Song (Chemical Engineering Journal, 2026)

Interaction of SFPQ with S100A8 and S100A9 in EoL-1 and EoL-1-IR cells - Jae Ha Baek; Geunyeong Kim; Yujin Hong; Min Hwa Hong; Ji-Sook Lee; Ik-Chan Song; Soo-Jung Gong; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Reducing greenhouse gas emissions while improving rice yield and water use efficiency in rice paddies through mid-season drainage and intermittent irrigation - Su-Heon Jang; Jae-In Lee; Chang-Gu Lee; Gil Won Kim; Jin-Kyung Hong; Seong-Jik Park (Agriculture, Ecosystems & Environment, 2026)

Formation processes and quality evaluation of natural zeolite deposits in dynamic diagenetic systems of the Janggi Basin, southeastern Korea: implications for zeolite ore exploration - Changyun Park; Hae-in Lee; Jae-Hwan Kim; Donghoon Chung; Yongmoon Lee; Soojin Lee; Tae-Hee Koo; Insung Kang; Ho Sim; Woohyun Choi; Sung Man Seo (Mineralium Deposita, 2026)

AI-driven non-intrusive occupant monitoring for occupant-centric control: A multi-domain review of thermal, air, and visual environments - Ji Young Yun; Jin Woo Moon; Kang Woo Bae; Jun Kyu Kim; Hae Won Lee; Hye In Kim; Jae Ho Sung; Michael Kim (Building and Environment, 2026)

Characterisation and mechanism of action of the antimicrobial activity of hetero-exopolysaccharide from Lentilactobacillus buchneri KU200793 against Staphylococcus aureus and Listeria monocytogenes - Manoj Kumar Yadav; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Young-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae-Kyung Kang (Archives of Microbiology, 2026)

Ammonia Emissions and Crop Yields in Upland Fields Cultivating Chinese Cabbage and Potato Using Solid and Liquid Manure Compost - Oyunerdene Boldsaikhan; Eun-Chae Im; Jae-In Lee; Chang-Gu Lee; Seong-Jik Park (Water, Air, & Soil Pollution, 2026)

A Fucose-containing Hetero-exopolysaccharide From Levilactobacillus brevis B151 Exhibits Potent Antimicrobial, Antibiofilm, and Antioxidant Activities - Manoj Kumar Yadav; Remilyn M. Mendoza; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Yeong-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae‑Kyung Kang (Probiotics and Antimicrobial Proteins, 2026)

Ubiquilin 1 Inhibits intracellular proliferation of Salmonella enterica serovar Typhimurium through Xenophagy - In Sook Jeon; Yong-Hee Lee; Jin Tae Hong; Won Seop Kim; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2026)

First report of Diaporthe nobilis causing trunk canker on Quercus myrsinifolia Blume (evergreen oaks; Fagaceae) in Korea - Vantha Choub; Ju-Yeol Yun; Su-In Choi; Su-Yeon Lee; Jae-Hyun Moon; Henry B. Ajuna; Eun-Young Yim; Young Sang Ahn (Journal of Plant Pathology, 2026)

Corrigendum to ‘Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications’ [Environ. Pollut. 377 (2025) 126428] - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2026)

A fully automatic, high-throughput, all-in-one centrifugal microfluidic workstation integrated with a Switching-PCR assay for rapid respiratory virus diagnostics - Vu Minh Phan; Min Young Lee; Hiep Van Nguyen; Thanh Hoai Nguyen; Yee Hyung Kim; Sae Rom Kim; Jae-Hoon Lee; Sun-Woo Kim; Woo In Lee; Tae Seok Seo (Chemical Engineering Journal, 2026)

Field evaluation of ammonia emissions, yield performance, and profitability under four nitrogen fertilizers in vegetable cultivation - Oyunerdene Boldsaikhan; Eun-Chae Im; Jae-In Lee; Chang-Gu Lee; Seong-Jik Park (Atmospheric Pollution Research, 2026)

Current contamination trends and historical records of traditional and emerging polycyclic aromatic hydrocarbons in sediments from Yeongil Bay and Hupo Region, East Sea - Jihyun Cha; Chang-Eon Lee; Mungi Kim; Youngnam Kim; Jiyun Gwak; Dong Jin Joe; Jae-Hyun Lim; In Kwon Um; Man Sik Choi; Seongjin Hong (Marine Pollution Bulletin, 2026)

Flame-constructed spinel Fe-Ni-O nanoparticles-on-nanosheet superstructures for scalable and durable hydrogen production - Jin Sil Kim; Sung Won Hwang; Yoo Jae Jeong; Runfa Tan; Ha Min Lee; Arumugam Sivanantham; In Sun Cho (Chemical Engineering Journal, 2026)

Evaluation and application of molecular marker sets for developing PHS-resistant wheat in Korea - Hyeonjin Park; Jin-Kyung Cha; So-Myeong Lee; Youngho Kwon; Woo-Jae Kim; Jong-Hee Lee; In-Jung Lee (Euphytica, 2026)
Pre-harvest sprouting (PHS) is a major constraint on wheat production in Korea, reducing grain quality and end-use value. To accelerate the development of PHS-resistant cultivars with improved agronomic performance, we employed a marker-assisted backcrossing (MABC) approach using molecular markers previously reported in the literature. For foreground selection, 81 molecular markers (74 KASP and 7 gel-based) targeting key genes related to PHS resistance, grain quality, and disease resistance were applied. Genome-wide background selection was conducted with 547 KASP markers to monitor recovery of the recurrent parent genome. Genotyping of 94 wheat accessions revealed distinct genetic clustering among domestic cultivars, introduced germplasm, and 1BL.1RS rye translocation lines, demonstrating the effectiveness of the marker set in capturing genome-wide diversity. Using MABC combined with speed breeding, three elite lines were developed by pyramiding favorable alleles from ‘Joongmo2008’ and ‘Tapdong’. Among them, ‘Milyang55’ exhibited strong PHS resistance (germination rate: 21.1%), desirable agronomic traits, and flour quality comparable to ‘Joongmo2008’. Donor genome proportions ranged from 25.5 to 43.0%, confirming efficient recovery of the recurrent parent genome. These results highlight the utility of integrating pre-selected molecular markers with MABC and speed breeding for the rapid development of elite wheat cultivars with improved PHS resistance and end-use quality.

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Characterization and comparative analysis of saponins in various spinach (Spinacia oleracea L.) cultivars according to growing seasons - Su-Yeon Lee; Doo-Young Kim; Hyun-Jae Jang; Seon Min Oh; Hyoung-Geun Kim; Jongmin Ahn; In-Seo Heo; Heung Joo Yuk; Eun Kyoung Seo; Sei-Ryang Oh; Hyung Won Ryu (Food Chemistry, 2025)

Development of nutrient management system based on ion-equivalent concentration ratio and ion monitoring to maintain ionic balance in closed hydroponic solution - Min-Seok Gang; Hak-Jin Kim; Tae In Ahn; Woo-Jae Cho; Sang-Hyun Lee; Ju Young Lee; Ji-Eun Hwang (Computers and Electronics in Agriculture, 2025)

Visible light-driven selective redirection of phenolic carbon in heterogeneous Fenton-like reaction - Youn-Jun Lee; Prakash Govindaraj; Yoo Jae Jeong; Runfa Tan; In Sun Cho; Seong-Jik Park; Hern Kim; Chang-Gu Lee; Pedro J.J. Alvarez (Water Research, 2025)

Emergence of a conjugative hybrid plasmid co-harboring mcr-1.1, mcr-3.39, and tet(X4) in Escherichia coli from wastewater in Seoul: A potential threat to last-line antibiotics - Jin Seok Kim; Young Hee Jin; Jinwoo Kim; Chang-Kyu Kim; Sook Hyun Park; Ahryung Oh; YoungAh Yoo; Jae In Lee; Jihun Jung (Science of The Total Environment, 2025)

Green utilization of Meretrix lusoria shell for phosphorus removal, pathogenic bacteria inactivation, and phosphorus supply for crop growth - Su-Heon Jang; Jae-In Lee; Chuluuntsetseg Jadamba; Heejin Yang; Chang-Gu Lee; Soo-Cheul Yoo; Seong-Jik Park (Journal of Water Process Engineering, 2025)

Beyond ion size: How phase transitions in NaBi batteries enable superior rate performance to LiBi counterparts - Young-Hoon Kim; Yeong-In Yoon; Xiangmei Li; Young-Kwon Kim; Haiwon Lee; Jae-Chul Lee; Yong-Seok Choi (Chemical Engineering Journal, 2025)

Comparison of ammonia volatilization and crop growth in upland fields fertilized with urea and latex-coated fertilizer - Yeon-Jin Lee; Eun-Chae Im; Jae-In Lee; Chang-Gu Lee; Seong-Jik Park (Journal of Soils and Sediments, 2025)

Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2025)

Immunomodulation Effects of Porcine Cartilage Acellularized Matrix (pCAM) for Osteoarthritis Treatment - Ji Seob Kim; Hyeon Jae Kwon; In Sun Hwang; Young Hwa Lee; Kyung-Noh Yoon; Hee-Woong Yun; Jae-Hyeok Jang; Seo Jeong Kim; Zhoodatova Aiana; Seungwoo Kim; Minhee Moon; Bongki Kim; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Isotopic fractionation of gaseous mercury in a large industrial city: Spatio-temporal variations and source apportionment - In-Gyu Cho; Hoin Lee; Sae Yun Kwon; Min-Jae Jo; Dong-Woon Hwang; Jae-Hyun Lim; Sung-Deuk Choi (Journal of Hazardous Materials, 2025)

Defect-engineered black indium oxide: A high-performance photothermal material for solar-driven water purification - Runfa Tan; Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Mukkath Joseph Josline; Jae Yeong Lee; Jong Seong Bae; Arumugam Sivanantham; Yoo Jae Jeong; Jae-Hyun Lee; Sangwook Lee; In Sun Cho (Desalination, 2025)

Development of advanced polyacrylonitrile fiber-based adsorbents for heavy metal ion removal through electron beam irradiation followed by amination - Minho Son; Jong-Seok Park; Sung-In Jeong; Byoung-Min Lee; Jae-Hak Choi; Joon-Pyo Jeun (Journal of Water Process Engineering, 2025)

Fabrication of Fe-doped biochar for Pb adsorption through pyrolysis of agricultural waste with red mud - Jae-In Lee; Dongho Choi; Seungwon Kim; Seong-Jik Park; Eilhann E. Kwon (Chemosphere, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Arvimicrobium flavum gen. nov., sp. nov., A Novel Genus in the Family Phyllobacteriaceae Isolated From Forest Soil - Hyosun Lee; Dhiraj Kumar Chaudhary; Ki-Eun Lee; In-Tae Cha; Won-Jae Chi; Sunho Park; Taegun Seo; Dong-Uk Kim (Current Microbiology, 2025)

Jannaschia ovalis sp. nov., a marine bacterium isolated from a tidal flat sediment in the Republic of Korea - Dae Young Kwon; Sang Hyun Lee; Jong Seong Khim; Xiaoyue Xu; Bogun Kim; In-Geol Choi; Yeonjae Yoo; Jae-Jin Kim (Antonie van Leeuwenhoek, 2025)

Role of Rab proteins in PFOA-induced changes in boar sperm motility and capacitation - Seung-Ik Jang; Jae-Hwan Jo; Claudine Uwamahoro; Eun-Ju Jung; Woo-Jin Lee; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Joonho Moon; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Evaluation of large-scale poultry manure-derived biochar for efficient cadmium removal in zinc smelter wastewater - Jae-In Lee; Su-Heon Jang; Changsup Kim; Jin-Kyu Kang; Chang-Gu Lee; Seong-Jik Park (Journal of Environmental Management, 2024)

Artemisiae Iwayomogii Herba mitigates excessive neuroinflammation and Aβ accumulation by regulating the pro-inflammatory response and autophagy-lysosomal pathway in microglia in 5xFAD mouse model of Alzheimer’s disease - In Gyoung Ju; Seungmin Lee; Hyeri Im; Jae Hoon Kim; Hyeyoon Eo; Myung Sook Oh (GeroScience, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Nationwide evaluation of microplastic properties in municipal wastewater treatment plants in South Korea - Jae-Ho Lee; So-Jeong Cheon; Chang-Soo Kim; Soo-Hyun Joo; Ki-In Choi; Dong-Hwan Jeong; Soo-Hyung Lee; Jeong-Ki Yoon (Environmental Pollution, 2024)

Harnessing wood bottom ash for efficient arsenic removal from wastewater: Adsorption mechanisms and process optimisation - Jae-In Lee; Yohan Jeong; Youn-Jun Lee; Chang-Gu Lee; Seong-Jik Park (Chemosphere, 2024)

Enhancing machine learning models for total organic carbon prediction by integrating geospatial parameters in river watersheds - Haeseong Oh; Ho-Yeon Park; Jae In Kim; Byung Joon Lee; Jung Hyun Choi; Jin Hur (Science of The Total Environment, 2024)

Enhancing acetaminophen removal through persulfate activation with ZnCl2-SPI biochar: A study on reactive oxygen species contribution according to acetaminophen concentration - Heejin Yang; Gyu-Ri Choi; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Chemical Engineering Journal, 2024)

Design and Simulation-Based Validation of an AI Model for Predicting Grab-Type Ship Unloader Operation Data - Ga-Eun Jung; Woo-Hee Jeong; Seok-Ju Lee; Jae-In Lee; Tae-Won Kim; Hae-Jin Sung (Journal of Marine Science and Engineering, 2024)
Along with seaports automation, there is growing interest in the automation of Grab-Type Ship Unloader (GTSU) that unloads coal and iron ore from bulk carriers. Autonomous unloading operations of GTSU offer the potential for significant productivity improvement and cost savings. In this paper, an AI model trained with manual operation data was designed for GTSU automation operation, and the AI model was verified through the equation-of-motion-based GTSU operation simulator. The operation data of hoist, grab, and trolley were predicted by training the designed AI model with the manual operation data of GTSU. Before applying the predicted data to the actual equipment, the predicted driving data was verified using the equation-of-motion-based GTSU operation simulator. The AI prediction model was designed using the Multi-Layer Perception network, a type of artificial neural network. The AI prediction model was evaluated with the Mean-Squared Error indicator, and the validation loss was found to be less than 0.02. In addition, verification of the prediction data was performed using the GTSU dynamics-based simulator. The Mean Relative Error was up to 0.50, and the R2 score value exceeded 0.92, indicating that the model is effective in predicting operation data. The proposed AI prediction model will be effectively utilized to implement a fully automated unloading system.

Ether vs. Carbonate solvents in Na–CuS Batteries: Impact on anode Morphology, SEI Formation, and desolvation dynamics - Young-Hoon Kim; Son-Jae Sim; Yeong-In Yoon; Yong-Seok Choi; Hong-Kyu Kim; Jae-Chul Lee (Chemical Engineering Journal, 2024)

Natural peloids originating from subsea depths of 200 m in the hupo basin, South Korea: physicochemical properties for potential pelotherapy applications - Changyun Park; Jae-Hwan Kim; Woohyun Choi; Daeyoung Kim; Sang-Gun No; Donghoon Chung; Hae-in Lee; Seungbin Seo; Sung Man Seo (Environmental Geochemistry and Health, 2024)
The present study firstly reports surface sediment from the subsea depth of 200 m as a potential natural peloid. The fine-silt sediment exhibited a consistent clay mineral composition dominated by illite, chlorite, kaolinite, and diatomite. The most abundant clay mineral was illite/mica, with other minerals loosely packed in a face-to-face orientation. The thermal conductivity, specific heat capacity, and cation-exchange capacity of the sediment were in the range 0.855–0.885 W/m K, 2.718–2.821 J/g °C, and 23.06–32.96 cmol/kg, respectively. The concentrations of most toxic elements in the sediment were considerably lower than the limits set by domestic cosmetic regulations and other international standards. The analyzed samples exhibited similar properties to those of previously reported peloids, thus making them suitable for use in the field of pelotherapy; furthermore, the consistency in data across a wide peloid-distribution area is expected to enable economically viable mining. Future investigations should aim to to evaluate the long-term effects on the skin, the bioavailability of potentially hazardous substances, and the therapeutic efficacy for various skin conditions.

Feasibility study of Aesculus turbinata fruit shell-derived biochar for ammonia removal in wastewater and its subsequent use as nitrogen fertilizer - Jae-In Lee; Chuluuntsetseg Jadamba; Chang-Gu Lee; Sung-Chang Hong; Jin-Ho Kim; Soo-Cheul Yoo; Seong-Jik Park (Chemosphere, 2024)

A sustainable bioprocessing system leveraging gas fermentation and bipolar membrane electrodialysis system for direct recovery of acetic acid - Mungyu Lee; Jae-Hun Kim; Muhammad Yasin; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2024)

Correction to: Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)

Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)
With the increasing use of flattening filter free (FFF) beams, it is important to evaluate the impact on the skin dose and target coverage of breast cancer treatments. This study aimed to compare skin doses of treatments using FFF and flattening filter (FF) beams for breast cancer. The study established treatment plans for left breast of an anthropomorphic phantom using Halcyon’s 6-MV FFF beam and TrueBeam’s 6-MV FF beam. Volumetric modulated arc therapy (VMAT) with varying numbers of arcs and intensity modulated radiation therapy (IMRT) were employed, and skin doses were measured at five points using Gafchromic EBT3 film. Each measurement was repeated three times, and averaged to reduce uncertainty. All plans were compared in terms of plan quality to ensure homogeneous target coverage. The study found that when using VMAT with two, four, and six arcs, in-field doses were 19%, 15%, and 6% higher, respectively, when using Halcyon compared to TrueBeam. Additionally, when using two arcs for VMAT, in-field doses were 10% and 15% higher compared to four and six arcs when using Halcyon. Finally, in-field dose from Halcyon using IMRT was about 1% higher than when using TrueBeam. Our research confirmed that when treating breast cancer with FFF beams, skin dose is higher than with traditional FF beams. Moreover, number of arcs used in VMAT treatment with FFF beams affects skin dose to the patient. To maintain a skin dose similar to that of FF beams when using Halcyon, it may be worth considering increasing the number of arcs.

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Graphitic-carbon-nitride-hydrophilicity-dependent photocatalytic degradation of antibiotics with different log Kow - Jong-Min Lee; Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Eun Hea Jho; Seong-Jik Park; Chang-Gu Lee (Chemosphere, 2024)

Developing a sorptive material of cadmium from pyrolysis of hen manure - Jae-In Lee; Dongho Choi; Seungwon Kim; Jee Young Kim; Seong-Jik Park; Eilhann E. Kwon (Chemosphere, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Proton pump inhibitors associated with an increased risk of mortality in elderly: a systematic review and meta-analysis - Hyun Jin Song; Hyun-Ju Seo; Xinyi Jiang; Nakyung Jeon; Yoon Jae Lee; In-Hyuk Ha (European Journal of Clinical Pharmacology, 2024)

Protective effect of Luffa cylindrica Roemer against dexamethasone-induced muscle atrophy in primary rat skeletal muscle cells - Changhwan Yeo; Hyunseong Kim; Wan-Jin Jeon; Junseon Lee; Jin Young Hong; Hyun Kim; Yoon Jae Lee; Seung Ho Baek; In-Hyuk Ha (Journal of Muscle Research and Cell Motility, 2024)
Glucocorticoids (GCs) are commonly used in the treatment of chronic inflammatory conditions. However, the administration of high doses and long-term use of GCs can induce muscle atrophy (MA) in patients, leading to a decline in quality of life and increased mortality. MA leads to protein degradation in skeletal muscle, resulting in a reduction of muscle mass. This process is triggered by GCs like dexamethasone (DEX), which induce the expression of E3 ubiquitin ligases, namely Atrogin-1 and muscle RING-finger protein-1 (MuRF1). In this study, we examined the anti-MA potential of Luffa cylindrica Roemer (LCR) on DEX-treated primary skeletal myotubes. Primary skeletal myotubes stimulated with LCR alone resulted in a significant upregulation of myotube development, characterized by an increase in both the number and diameter of myotubes. Contrastingly, combined treatment with LCR and DEX reduced the expression of Atrogin-1, while treatment with DEX alone induced the expression of MuRF1. Furthermore, LCR treatment successfully restored the number and diameter of myotubes that had been diminished by DEX treatment. These findings suggest that LCR holds potential for treating MA, as an accelerating effect on muscle development and anti-MA effects on primary skeletal muscle cells were observed.

Cancer screening through surface-enhanced Raman spectroscopy fingerprinting analysis of urinary metabolites using surface-carbonized silver nanowires on a filter membrane - Ho-Jae Yu; Eunji Jang; Ayoung Woo; In Woong Han; Hwang Gyun Jeon; Vo Thi Nhat Linh; Sung-Gyu Park; Ho Sang Jung; Min-Young Lee (Analytica Chimica Acta, 2024)

Probiotic, Paraprobiotic, and Hydrolyzed Yeast Mixture Supplementation Has Comparable Effects to Zinc Oxide in Improving Growth Performance and Ameliorating Post-weaning Diarrhea in Weaned Piglets - De Xin Dang; Si Yeong Choi; Young Jae Choi; Jong Hwa Lee; Mathieu Castex; Eric Chevaux; David Saornil; Fernando Bravo de Laguna; Guillermo Jimenez; In Ho Kim (Probiotics and Antimicrobial Proteins, 2024)

Perfluorooctanoic acid suppresses sperm functions via abnormal Protein Kinase B activation during capacitation - Seung-Ik Jang; Jae-Hwan Jo; Eun-Ju Jung; Woo-Jin Lee; Ju-Mi Hwang; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Anti-inflammatory and relaxation effects of Ulmus pumilla L. on EGF-inflamed bronchial epithelial and asthmatic bronchial smooth muscle cells - In-Seung Lee; Yeonjung Choi; Wona Jee; Jihyuk Park; Hyungsuk Kim; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2024)

Performance comparison of photodynamic antimicrobial chemotherapy with visible-light-activated organic dyes: Rose bengal, crystal violet, methylene blue, and toluidine blue O - Jae Hak Shin; Sang Bin Jeong; In Ho Kim; Seung Yeon Lee; Gi Byoung Hwang; Inyong Park; Ki Joon Heo; Jae Hee Jung (Environmental Research, 2023)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

The inhibitory mechanism of humic acids on photocatalytic generation of reactive oxygen species by TiO2 depends on the crystalline phase - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Chang-Gu Lee; Seong-Jik Park; Pedro J.J. Alvarez (Chemical Engineering Journal, 2023)

Development and authentication of Panax ginseng cv. Sunhong with high yield and multiple tolerance to heat damage, rusty roots and lodging - Jiho Seo; Joon-Soo Lee; Sung-Lye Shim; Jun-Gyo In; Chol-Soo Park; Yong-Jae Lee; Hee-Jun Ahn (Horticulture, Environment, and Biotechnology, 2023)

Cycling of phosphorus from wastewater to fertilizer using wood ash after energy production - Jae-In Lee; Chuluuntsetseg Jadamba; Soo-Cheul Yoo; Chang-Gu Lee; Myung-Chul Shin; Jechan Lee; Seong-Jik Park (Chemosphere, 2023)

Vulnerability assessment of Korean fisheries to climate change - Moo-Jin Kim; Jae-Beum Hong; In-Seong Han; Joon-Soo Lee; Do-Hoon Kim (Marine Policy, 2023)

Detection of microplastic traces in four different types of municipal wastewater treatment plants through FT-IR and TED-GC-MS - Jae-Ho Lee; Min-Jung Kim; Chang-Soo Kim; So-Jeong Cheon; Ki-In Choi; Juyang Kim; Jaehak Jung; Jeong-Ki Yoon; Soo-Hyung Lee; Dong-Hwan Jeong (Environmental Pollution, 2023)

First report of powdery mildew caused by Erysiphe deutziae on Deutzia parviflora in Korea - Kui-Jae Lee; In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

Value-added application of cattle manure bottom ash for phosphorus recovery from water and replenishment in soil - Jae-In Lee; Chuluuntsetseg Jadamba; Soo-Cheul Yoo; Chang-Gu Lee; Seong-Jik Park (Journal of Environmental Management, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Correction to: Prediction of future weight change with the dopamine transporter - Kyoungjune Pak; Keunyoung Kim; Myung Jun Lee; Jae Meen Lee; Bum Soo Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2023)

Facile synthesis of N vacancy g-C3N4 using Mg-induced defect on the amine groups for enhanced photocatalytic •OH generation - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Pedro J.J. Alvarez (Journal of Hazardous Materials, 2023)

Modeling for the estimating the adsorption property of fruit waste-based biosorbents for the removal of organic micropollutants - Bo-Gyeon Cho; Jae-Ho Lee; Hye-In Kim; Se-Been Mun; Se-Ra Jin; Dae Geun Kim; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Research, 2023)

Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants - Hee Jung Kim; Gill Sang Han; Jaesung Kim; Young Ju Kim; Jin Hyuk Choi; Jae Myeong Lee; Geon Woo Yoon; Hongshin Lee; In Sun Cho; Jaesang Lee; Hyun Suk Jung (Journal of Water Process Engineering, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Melatonin alleviates arsenic (As) toxicity in rice plants via modulating antioxidant defense system and secondary metabolites and reducing oxidative stress - Rahmatullah Jan; Saleem Asif; Sajjad Asaf; Lubna; Xiao-Xuan Du; Jae-Ryoung Park; Kim Nari; Dibya Bhatta; In-jung Lee; Kyung-Min Kim (Environmental Pollution, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

High-flux CO2 separation using thin-film composite polyether block amide membranes fabricated by transient-filler treatment - Chae-Young Park; Chang-In Kong; Eun-Young Kim; Chang-Ha Lee; Ki-Suk Kim; Jae-Hyeok Lee; Jongmyeong Lee; Su-Young Moon (Chemical Engineering Journal, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Identification of CRISPR-Induced Mutations in Plants: with a Focus on the Next-Generation Sequencing Assay - Jae-Young Yun; Si-in Yu; Seung-eun Bang; Jae-Yeon Kim; Sang Ho Lee; Byeong-ha Lee (Journal of Plant Biology, 2022)

Improvement of fluid penetration in soil by plasma blasting - Hyun-Sic Jang; In-Joon Baek; Jae-Yong Song; Geun-Chun Lee; Bo-An Jang (Geosciences Journal, 2022)

Double-blind randomized placebo-controlled study of the efficacy and safety of hair loss prevention shampoo containing salicylic acid, panthenol, and niacinamide in alopecia patients - Hee-Taek Kim; Hye-Su Park; Yong-Min Kim; In-Chul Lee; Sang-Jun Lee; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2022)

PKC-β modulates Ca2+ mobilization through Stim1 phosphorylation - Hye-Jin Song; In-Sook Jeon; Seung Ryul Kim; Kwan Sik Park; Jae-Won Soh; Kwang Youl Lee; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2022)
Background Calcium ions play a pivotal role in cell proliferation, differentiation, and migration. Under basal conditions, the calcium level is tightly regulated; however, cellular activation by growth factors increase the ion level through calcium pumps in the plasma membrane and endoplasmic reticulum for calcium signaling. Orai1 is a major calcium channel in the cell membrane of non-excitable cells, and its activity depends on the stromal interaction molecule 1 (Stim1). Several groups reported that the store-operated calcium entry (SOCE) can be modulated through phosphorylation of Stim1 by protein kinases such as extracellular signal-regulated kinase (ERK), protein kinase A (PKA), and p21-activated kinase (PAK). PKC is a protein kinase that is activated by calcium and diacylglycerol (DAG), but it remains unclear what role activated PKC plays in controlling the intracellular calcium pool. Objectives Here, we investigated whether PKC-β controls intracellular calcium dynamics through Stim1. Methods Several biochemical methods such as immune-precipitation, site directed mutagenesis, in vitro kinase assay were employed to investigate PKC interaction with and phosphorylation of Stim1. Intracellular calcium mobilization, via Stim1 mediated SOCE channel, were studied using in the presence of PKC activator or inhibitor under a confocal microscope. Results Our data demonstrate that PKC interacts with and phosphorylates Stim1 in vitro. phosphorylation of Stim1 at its C-terminal end appears to be important in the regulation of SOCE activity in HEK293 and HeLa cells. Additionally, transient intracellular calcium mobilization assays demonstrate that the SOCE activity was inhibited by PKC activators or activated by PKC inhibitors. Conclusion In sum, our data suggest a repressive role of PKC in regulating calcium entry through SOCE.

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Electron transport and photosynthetic performance in Fragaria × ananassa Duch. acclimated to the solar spectrum modified by a spectrum conversion film - Jun Hyeun Kang; Hyo In Yoon; Jae Moon Lee; Jae Pil Kim; Jung Eek Son (Photosynthesis Research, 2022)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

First report of rust caused by Coleosporium zanthoxyli on Zanthoxylum piperitum in Korea - Young-Joon Choi; Jae-Sung Lee; In-Young Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

Functional dissection of the phosphotransferase system provides insight into the prevalence of Faecalibacterium prausnitzii in the host intestinal environment - Deborah Kang; Hyeong‐In Ham; Seung‐Hwan Lee; Yong‐Joon Cho; Yeon‐Ran Kim; Chang‐Kyu Yoon; Yeong‐Jae Seok (Environmental Microbiology, 2021)
Summary Faecalibacterium prausnitzii is a dominant member of healthy human colon microbiota, regarded as a beneficial gut bacterium due to its ability to produce anti‐inflammatory substances. However, little is known about how F. prausnitzii utilizes the nutrients present in the human gut, influencing its prevalence in the host intestinal environment. The phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS) is a widely distributed and highly efficient carbohydrate transport system found in most bacterial species that catalyses the simultaneous phosphorylation and import of cognate carbohydrates; its components play physiological roles through interaction with other regulatory proteins. Here, we performed a systematic analysis of the 16 genes encoding putative PTS components (2 enzyme I, 2 HPr, and 12 enzyme II components) in F. prausnitzii A2‐165. We identified the general PTS components responsible for the PEP‐dependent phosphotransfer reaction and the sugar‐specific PTS components involved in the transport of two carbohydrates, N ‐acetylglucosamine and fructose, among five enzyme II complexes. We suggest that the dissection of the functional PTS in F. prausnitzii may help to understand how this species outcompetes other bacterial species in the human intestine.

Fluoride removal by thermally treated egg shells with high adsorption capacity, low cost, and easy acquisition - Jae-In Lee; Seung-Hee Hong; Chang-Gu Lee; Seong-Jik Park (Environmental Science and Pollution Research, 2021)

Mesenchymal Stem Cells Derived from Wharton’s Jelly Can Differentiate into Schwann Cell-Like Cells and Promote Peripheral Nerve Regeneration in Acellular Nerve Grafts - Soon Jin Choi; Suk Young Park; Young Ho Shin; Seung-Ho Heo; Kang-Hyun Kim; Hyo In Lee; Jae Kwang Kim (Tissue Engineering and Regenerative Medicine, 2021)

Fucoxanthin biosynthesis has a positive correlation with the specific growth rate in the culture of microalga Phaeodactylum tricornutum - Do Yeon Kwon; Trang Thi Vuong; Jaeyoung Choi; Taek Sung Lee; Jae-In Um; Song Yi Koo; Keum Taek Hwang; Sang Min Kim (Journal of Applied Phycology, 2021)

Korea Institute of Ocean Science and Technology Earth System Model and Its Simulation Characteristics - Gyundo Pak; Yign Noh; Myong-In Lee; Sang-Wook Yeh; Daehyun Kim; Sang-Yeob Kim; Joon-Lee Lee; Ho Jin Lee; Seung-Hwon Hyun; Kwang-Yeon Lee; Jae-Hak Lee; Young-Gyu Park; et al. (Ocean Science Journal, 2021)

Injectable Hydrogel Containing Tauroursodeoxycholic Acid for Anti-neuroinflammatory Therapy After Spinal Cord Injury in Rats - Gong Ho Han; Seong Jun Kim; Wan-Kyu Ko; Daye Lee; Jae Seo Lee; Haram Nah; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

4-MeO-PCP and 3-MeO-PCMo, new dissociative drugs, produce rewarding and reinforcing effects through activation of mesolimbic dopamine pathway and alteration of accumbal CREB, deltaFosB, and BDNF levels - Arvie Abiero; Chrislean Jun Botanas; Raly James Custodio; Leandro Val Sayson; Mikyung Kim; Hyun Jun Lee; Hee Jin Kim; Kun Won Lee; Youngdo Jeong; Joung-Wook Seo; In Soo Ryu; Yong Sup Lee; et al. (Psychopharmacology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

A Yellow Sea Monitoring Platform and Its Scientific Applications - Yong Sun Kim; Chan Joo Jang; Jae Hoon Noh; Kyung-Tae Kim; Jae-Il Kwon; Yongchim Min; Jongmin Jeong; Jaeik Lee; In-Ki Min; Jae-Seol Shim; Do-Seong Byun; Jinkwon Kim; et al. (Frontiers in Marine Science, 2019)

The Reduction of the Global Irradiance Due to the Asian Dust Aerosols (PM10) Estimated by the Observed Data in the Dust Source Region of Erdene in Mongolia - Soon-Ung Park; Seung Jin Joo; In-Hye Lee; Jae-Won Ju (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Prevention and relaxation effects of Liriope platyphylla on bronchial asthma in vitro model by suppressing the activities of MAPK/NF-κB pathway - In-Seung Lee; Dong-Hyun Kim; Kang-Hoon Kim; Jiyoung Park; Yumi Kim; Eun-Jin An; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2019)

Prediction of future weight change with the dopamine transporter - Kyoungjune Pak; Keunyoung Kim; Myung Jun Lee; Jae Meen Lee; Bum Soo Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

The Effect of Probiotics on Halitosis: a Systematic Review and Meta-analysis - Jun-Il Yoo; In-Soo Shin; Jae-Gyu Jeon; Yeon-Mi Yang; Jae-Gon Kim; Dae-Woo Lee (Probiotics and Antimicrobial Proteins, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Improvement of blood culture contamination rate, blood volume, and true positive rate after introducing a dedicated phlebotomy team - Moonsuk Bae; Hae In Kim; Joung Ha Park; Byung-Han Ryu; Jeonghyun Chang; Heungsup Sung; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes - Hyo-In Choi; Jung Ae Hong; Min-Seok Kim; Sang Eun Lee; Sung-Ho Jung; Pil Whan Yoon; Joon Seon Song; Jae-Joong Kim (Cardiovascular Toxicology, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

Practice Patterns in Distinguishing Between Background Pain and Breakthrough Pain During Patient Education: a Korean Physician Survey - Jinyoung Shin; Do Yeun Kim; Juneyoung Lee; Youn Seon Choi; In Gyu Hwang; Sun Kyung Baek; Min Seok Seo; Jae Yong Shim (Journal of Cancer Education, 2018)

Spirosoma terrae sp. nov., Isolated from Soil from Jeju Island, Korea - Leonid N. Ten; Joseph Okiria; Jae-Jin Lee; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2018)

Matrix Metalloproteinase-8 Inhibition Prevents Disruption of Blood–Spinal Cord Barrier and Attenuates Inflammation in Rat Model of Spinal Cord Injury - Hemant Kumar; Min-Jae Jo; Hyemin Choi; Manjunatha S. Muttigi; Seil Shon; Byung-Joo Kim; Soo-Hong Lee; In-Bo Han (Molecular Neurobiology, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Development of RNA aptamer that inhibits methyltransferase activity of dengue virus - Jae In Jung; Seung Ryul Han; Seong-Wook Lee (Biotechnology Letters, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Erratum to: Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Anti-erythema and anti-edema activities of lactic acid bacteria extracts in mice - Jae-Suk Choi; Dan Bie Jang; Hye Kyung Cho; Bo-Bae Lee; Yu-Mi Ha; In Soon Choi (Toxicology and Environmental Health Sciences, 2017)

Deinococcus knuensis sp. nov., a bacterium isolated from river water - Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Leonid N. Ten; Hee-Young Jung (Antonie van Leeuwenhoek, 2017)

Development of regional uplift and uplift-related strata in Gunsan Basin, Yellow Sea: implications for Cenozoic crustal extension - Changyoon Lee; Young Jae Shinn; In-Chang Ryu (International Geology Review, 2016)

Chloroform induces cystein-rich 61, a mediator of collagen homeostasis via early growth response-1 dependent pathway in human skin dermal fibroblasts - Hana Lee; Jae Beom Park; Woo-In Ryu; Ji Hyun Kim; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

Toluene induces early growth response-1 dependent thymic stromal lymphopoietin expression in human keratinocytes - Hana Lee; Jae Beom Park; Hyu Cheol Bae; Woo-In Ryu; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

No association of CLOCK 3111T/C polymorphism with diurnal preference and sleep quality in Korean adults - Seong Jae Kim; Jung Hie Lee; Se Yong Lee; Jun-Won Hwang; In Bum Suh (Sleep and Biological Rhythms, 2016)

Whole-transcriptome analysis of mouse adipose tissue in response to short-term caloric restriction - Seung-Soo Kim; Kyung-Mi Choi; Soyoung Kim; Taesun Park; In-Cheol Cho; Jae-Won Lee; Cheol-Koo Lee (Molecular Genetics and Genomics, 2016)

Molecular analyses of H3N2 canine influenza viruses isolated from Korea during 2013–2014 - EunJung Lee; Eun-Ju Kim; Bo-Hye Kim; Jae-Young Song; In-Soo Cho; Yeun-Kyung Shin (Virus Genes, 2016)

Osteogenic differentiation of human mesenchymal stem cells promoted by the crude extracts of the mixture of Cortex mori radicis, Patrinia saniculaefolia - Koh-Woon Kim; In-Seung Lee; Won-Jae Lee; Jiyoung Park; Won Seok Chung; Jae-Heung Cho; Sung-Lim Lee; Hyeung-Jin Jang; Seok-Hee Chung (Molecular & Cellular Toxicology, 2015)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Genomic detection and characterization of a Korean isolate of Little cherry virus 1 sampled from a peach tree - Seungmo Lim; Davaajargal Igori; Ran Hee Yoo; Fumei Zhao; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Su-Heon Lee; Jae Sun Moon (Virus Genes, 2015)

Plant growth-promoting potential of endophytic fungi isolated from Solanum nigrum leaves - Abdur Rahim Khan; Ihsan Ullah; Muhammad Waqas; Raheem Shahzad; Sung-Jun Hong; Gun-Seok Park; Byung Kwon Jung; In-Jung Lee; Jae-Ho Shin (World Journal of Microbiology and Biotechnology, 2015)

Improvement in phytoremediation potential of Solanum nigrum under cadmium contamination through endophytic-assisted Serratia sp. RSC-14 inoculation - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Gun-Seok Park; Muhammad Waqas; Sung-Jun Hong; Byung Kwon Jung; Yunyoung Kwak; In-Jung Lee; Jae-Ho Shin (Environmental Science and Pollution Research, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

IAA Producing Enterobacter sp. I-3 as a Potent Bio-herbicide Candidate for Weed Control: A Special Reference with Lettuce Growth Inhibition - Jae-Man Park; Ramalingam Radhakrishnan; Sang-Mo Kang; In-Jung Lee (Indian Journal of Microbiology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Genetic characterization of porcine epidemic diarrhea virus in Korea from 1998 to 2013 - Seong-Hee Kim; Jung-Min Lee; Jongsun Jung; In-Joong Kim; Bang-Hun Hyun; Hyun-Il Kim; Choi-Kyu Park; Jae-Ku Oem; Yeon-Hee Kim; Myoung-Heon Lee; Kyoung-Ki Lee (Archives of Virology, 2015)

Molecular evolution of kobuviruses in cats - Yoon-Young Cho; Seong-In Lim; Yong Kwan Kim; Jae-Young Song; Joong-Bok Lee; Dong-Jun An (Archives of Virology, 2015)

Production of transgenic spermatozoa by lentiviral transduction and transplantation of porcine spermatogonial stem cells - Byung-Gak Kim; Yong-Hee Kim; Yong-An Lee; Bang-Jin Kim; Ki-Jung Kim; Sang-Eun Jung; Hak-Jae Chung; Seongsoo Hwang; Sun-Ho Choi; Myung Jick Kim; Dong-Hoon Kim; In Cheul Kim; et al. (Tissue Engineering and Regenerative Medicine, 2014)

DWD HYPERSENSITIVE TO UV-B 1 is negatively involved in UV-B mediated cellular responses in Arabidopsis - Sang-Hoon Kim; Hani Kim; Kyoung-In Seo; Soon-Hee Kim; Sunglan Chung; Xi Huang; Panyu Yang; Xing Wang Deng; Jae-Hoon Lee (Plant Molecular Biology, 2014)

Phosphate Solubilizing Bacillus megaterium mj1212 Regulates Endogenous Plant Carbohydrates and Amino Acids Contents to Promote Mustard Plant Growth - Sang-Mo Kang; Ramalingam Radhakrishnan; Young-Hyun You; Gil-Jae Joo; In-Jung Lee; Ko-Eun Lee; Jin-Ho Kim (Indian Journal of Microbiology, 2014)

Capsaicin suppresses the migration of cholangiocarcinoma cells by down-regulating matrix metalloproteinase-9 expression via the AMPK–NF-κB signaling pathway - Gong-Rak Lee; Soo Hwa Jang; Chang Jae Kim; Ah-Ram Kim; Dong-Joon Yoon; Neung-Hwa Park; In-Seob Han (Clinical & Experimental Metastasis, 2014)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Transcriptome information of the Arctic green sea urchin and its use in environmental monitoring - Jae-Sung Rhee; Bo-Mi Kim; Beom-Soon Choi; Ik-Young Choi; Hyun Park; In-Young Ahn; Jae-Seong Lee (Polar Biology, 2014)

Silicon Application to Rice Root Zone Influenced the Phytohormonal and Antioxidant Responses Under Salinity Stress - Yoon Ha Kim; Abdul Latif Khan; Muhammad Waqas; Jae Kyoung Shim; Duck Hwan Kim; Kyeong Yeoll Lee; In Jung Lee (Journal of Plant Growth Regulation, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Safety, functionality and stability tests of Ecklonia cava extract for dermal application - Jae-Suk Choi; Kyungyong Lee; Bo-Bae Lee; Yang-Chun Kim; Kwang Keun Cho; In Soon Choi (Toxicology and Environmental Health Sciences, 2014)

3,4,5-Trihydroxycinnamic acid inhibits lipopolysaccharide (LPS)-induced inflammation by Nrf2 activation in vitro and improves survival of mice in LPS-induced endotoxemia model in vivo - Jae-Won Lee; Chang Jun Bae; Yong-Jun Choi; Song-In Kim; Yong-Soo Kwon; Hee Jae Lee; Sung-Soo Kim; Wanjoo Chun (Molecular and Cellular Biochemistry, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Expression of gibberellin 2-oxidase 4 from Arabidopsis under the control of a senescence-associated promoter results in a dominant semi-dwarf plant with normal flowering - Dong Hee Lee; In Chul Lee; Kook Jin Kim; Dong Su Kim; Hyung Jin Na; In-Jung Lee; Sang-Mo Kang; Hyung-Woo Jeon; Phi Yen Le; Jae-Heung Ko (Journal of Plant Biology, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Chloroform induces HIF-1α-dependent VEGF expression in human keratinocytes - Jae Jun Nam; Hana Lee; Hyun Cheol Bae; Jinhee Kim; Sang Hoon Jeong; Woo-In Ryu; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Fungal endophyte Penicillium janthinellum LK5 improves growth of ABA-deficient tomato under salinity - Abdul Latif Khan; Muhammad Waqas; Abdur Rahim Khan; Javid Hussain; Sang-Mo Kang; Syed Abdullah Gilani; Muhammad Hamayun; Jae-Ho Shin; Muhammad Kamran; Ahmed Al-Harrasi; Byung-Wook Yun; Muhammad Adnan; et al. (World Journal of Microbiology and Biotechnology, 2013)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

Phellinus baumii ethyl acetate extract alleviated collagen type II induced arthritis in DBA/1 mice - Taddesse Yayeh; Whi Min Lee; Dukhwan Ko; Seung-Choon Park; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Seung-Hyung Kim; Seung-Bok Hong; Suk Kim; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2013)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

N-terminal region of rice polycomb group protein OsEZ1 is required for OsEZ1–OsFIE2 protein interaction - Jong-Kuk Na; Mi-Hye Seo; Seok-Jun Moon; In-Sun Yoon; Yeon-Hee Lee; Jae Kwang Kim; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2013)

The relationship between antipsychotic D2 occupancy and change in frontal metabolism and working memory - Euitae Kim; Oliver D. Howes; Federico E. Turkheimer; Bo-Hyung Kim; Jae Min Jeong; Ji Who Kim; Jae Sung Lee; In-Jin Jang; Sang-Goo Shin; Shitij Kapur; Jun Soo Kwon (Psychopharmacology, 2013)

3′,4′-Dimethoxythioflavone induces endothelium-dependent vasorelaxation through activation of epidermal growth factor receptor - Eun Jin Jang; Young Mi Seok; Jae In Lee; Hyun Min Cho; Uy Dong Sohn; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Antisense-overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants - Eun Soo Seong; Ji Hye Yoo; Jae Geun Lee; Hee Young Kim; In Seong Hwang; Kweon Heo; Jae Kwang Kim; Jung Dae Lim; Erik J. Sacks; Chang Yeon Yu (Molecular Biology Reports, 2013)

Association of the gene encoding stearoyl-CoA desaturase (SCD) with fatty acid composition in an intercross population between Landrace and Korean native pigs - Dyah Maharani; Hee-Bok Park; Jae-Bong Lee; Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee (Molecular Biology Reports, 2013)

Synergistic Effect and Antibiofilm Activity Between the Antimicrobial Peptide Coprisin and Conventional Antibiotics Against Opportunistic Bacteria - In-sok Hwang; Jae-Sam Hwang; Ji Hong Hwang; Hyemin Choi; Eunjung Lee; Yangmee Kim; Dong Gun Lee (Current Microbiology, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Chondracanthus tenellus (Harvey) hommersand extract protects the human keratinocyte cell line by blocking free radicals and UVB radiation-induced cell damage - Mei Jing Piao; Yu Jae Hyun; Tae-Heon Oh; Hee Kyoung Kang; Eun Sook Yoo; Young Sang Koh; Nam Ho Lee; In Soo Suh; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2012)

Roles of various cullin-RING E3 ligases involved in hormonal and stress responses in plants - Kyoung-In Seo; Eunyoung Song; Sunglan Chung; Jae-Hoon Lee (Journal of Plant Biology, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A brown alga Sargassum fulvellum facilitates neuronal maturation and synaptogenesis - Md. Abdul Hannan; Ji-Young Kang; Yong-Ki Hong; HyunSook Lee; Muhammad Tanvir Hossain Chowdhury; Jae-Suk Choi; In Soon Choi; Il Soo Moon (In Vitro Cellular & Developmental Biology - Animal, 2012)

Simple freezing and thawing protocol for long-term storage of harvested fresh Undaria pinnatifida - Jae-Suk Choi; Bo-Bae Lee; Sun Ju An; Jae Hak Sohn; Kwang Keun Cho; In Soon Choi (Fisheries Science, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Characterization of phenotypic variants of Clavibacter michiganensis subsp. michiganensis isolated from Capsicum annuum - Kyu-Ock Yim; Hyok-In Lee; Jung-Hee Kim; Seung-Don Lee; Jung-Hee Cho; Jae-Soon Cha (European Journal of Plant Pathology, 2012)

Assessment of the APCC coupled MME suite in predicting the distinctive climate impacts of two flavors of ENSO during boreal winter - Hye-In Jeong; Doo Young Lee; Karumuri Ashok; Joong-Bae Ahn; June-Yi Lee; Jing-Jia Luo; Jae-Kyung E. Schemm; Harry H. Hendon; Karl Braganza; Yoo-Geun Ham (Climate Dynamics, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus - Abdul Latif Khan; Muhammad Hamayun; Ramalingam Radhakrishnan; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Jae-Ho Shin; Yeon-Sik Choo; Jong-Guk Kim; In-Jung Lee (Antonie van Leeuwenhoek, 2012)

Phellinus baumii ethyl acetate extract inhibits lipopolysaccharide-induced iNOS, COX-2, and proinflammatory cytokine expression in RAW264.7 cells - Taddesse Yayeh; Won Jun Oh; Seung-Choon Park; Tae-Hwan Kim; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Sang-Keun Kim; Seung-Bok Hong; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2012)

Hepatoprotection of different water extracts from Acer tegmentosum M. on CCl4-induced acute hepatotoxicity in mice: comparative efficacies between the extracts of boughs, twigs, and leaves - Kwang-Yong Shim; Dong-Heui Kim; Soon-Bong Song; Xu-Feng Qi; Yang-Suk Yoon; Hyun-Soo Kim; Jong-In Lee; Hwa-Eun Oh; Soo-Ki Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2011)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor - Suk-Min Ko; Hyeon-Jin Sun; Myung Jin Oh; In-Ja Song; Min-Jae Kim; Hyun-Sook Sin; Chang-Hyo Goh; Yong-Woo Kim; Pyung-Ok Lim; Hyo-Yeon Lee; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Isolation and characterization of 28 polymorphic SSR loci from castor bean (Ricinus communis L.) - Kyoung-In Seo; Gi-An Lee; Kyung-Ho Ma; Do-Yoon Hyun; Yong-Jin Park; Jong-Wook Jung; Sok-Young Lee; Jae-Gyun Gwag; Chung-Kon Kim; Myung-Chul Lee (Journal of Crop Science and Biotechnology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Autoinduction of a genetic locus encoding putative acyltransferase in Corynebacterium glutamicum - Hee-Sung Shin; Yong-Jae Kim; In-Hwa Yoo; Heung-Shick Lee; Shouguang Jin; Un-Hwan Ha (Biotechnology Letters, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Effect of toluene on RANTES and eotaxin expression through the p38 and JNK pathways in human lung epithelial cells - Yu-Ri Kim; In-Kyoung Kim; Sang-Hui Seo; Seung Ho Lee; Hee Ra Lee; Jae-Eun Pie; Meyoung-Kon Kim (Molecular & Cellular Toxicology, 2010)

Environmental quality of Korean coasts as determined by modified Shannon–Wiener evenness proportion - Jae-Won Yoo; Yong-Woo Lee; Jennifer L. Ruesink; Chang-Gun Lee; Chang-Soo Kim; Mi-Ra Park; Kon-Tak Yoon; In-Seo Hwang; Jun-Ho Maeng; Rutger Rosenberg; Jae-Sang Hong (Environmental Monitoring and Assessment, 2010)

Correlation between nutrition intake and gene expression profiles in children with asthma - Jae-Eun Pie; Yu-Ri Kim; In-Kyoung Kim; Sang-Hui Seo; Seung Ho Lee; Hee Ra Lee; Young Yoo; Ji Tae Chung; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Molecular & Cellular Toxicology, 2010)

Detection of replicating negative-sense RNAs in CaCo-2 cells infected with human astrovirus - So Young Jang; Weon Hwa Jeong; Mi Suk Kim; Young Min Lee; Jae In Lee; Gyu Cheol Lee; Soon Young Paik; Gwang Pyo Koh; Jong Min Kim; Chan Hee Lee (Archives of Virology, 2010)

Identification of a null allele of cytochrome P450 3A7: CYP3A7 polymorphism in a Korean population - Sang Seop Lee; Hyun-Ju Jung; Jung Soon Park; In-June Cha; Doo-Yeoun Cho; Jae-Gook Shin (Molecular Biology Reports, 2010)

Electricity generation coupled to oxidation of propionate in a microbial fuel cell - Jae Kyung Jang; In Seop Chang; Hwa Yeon Hwang; Yeng Fung Choo; JiYoung Lee; Kyung Suk Cho; Byung Hong Kim; Kenneth H. Nealson (Biotechnology Letters, 2010)

Gibberellin production by pure cultures of a new strain of Aspergillus fumigatus - Muhammad Hamayun; Sumera Afzal Khan; Mir Ajab Khan; Abdul Latif Khan; Sang-Mo Kang; Sang-Kuk Kim; Gil-Jae Joo; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

Propagation characteristics of historical tsunamis that attacked the east coast of Korea - Chae Ho Lim; Jae Seok Bae; Jong In Lee; Sung Bum Yoon (Natural Hazards, 2008)

Artificial neural networks for predicting DGPS carrier phase and pseudorange correction - Arif Indriyatmoko; Taesam Kang; Young Jae Lee; Gyu-In Jee; Yong Beom Cho; Jeongrae Kim (GPS Solutions, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Superoxide anion regulates plant growth and tuber development of potato - Mi-Sun Kim; Hyun-Soon Kim; Yoon-Shik Kim; Kwang-Hyun Baek; Hyun-Woo Oh; Kyu-Woong Hahn; Ro-Na Bae; In-Jung Lee; Hyouk Joung; Jae-Heung Jeon (Plant Cell Reports, 2007)

Primary Survey on Algal Community of Gyounggi Bay for Restoration - Wook-Jae Lee; Mi-Sook Hwang; Jae-Min Baek; Jae-Wan Lee; Join-In Kim (Algae, 2007)

Tissue expression and cellular localization of phospholipid hydroperoxide glutathione peroxidase (PHGPx) mRNA in male mice - In-Jeoung Baek; Dong-Suk Seo; Jung-Min Yon; Se-Ra Lee; Yan Jin; Sang Soep Nahm; Jae-Hwang Jeong; Young-Kug Choo; Jong-Koo Kang; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2007)

The Macroalgal Community of Bagryoungdo Island in Korea - Jae-Min Baek; Mi-Sook Hwang; Jae-Wan Lee; Wook-Jae Lee; Jong-In Kim (Algae, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

Sulindac-derived reactive oxygen species induce apoptosis of human multiple myeloma cells via p38 mitogen activated protein kinase-induced mitochondrial dysfunction - Sung-Keum Seo; Hyung-Chahn Lee; Sang-Hyeok Woo; Hyeon-Ok Jin; Doo-Hyun Yoo; Su-Jae Lee; Sungkwan An; Tae-Boo Choe; Myung-Jin Park; Seok-Il Hong; In-Chul Park; Chang-Hun Rhee (Apoptosis, 2007)

Angiotensin II type 1 receptor 1166A/C polymorphism in association with blood pressure response to exogenous angiotensin II - Hyeong-Seok Lim; Joo-Youn Cho; Dal-Seok Oh; Jae-Yong Chung; Kyoung-Sup Hong; Kyun-Seop Bae; Kyung-Sang Yu; Kyung-Hoon Lee; In-Jin Jang; Sang-Goo Shin (European Journal of Clinical Pharmacology, 2006)

Recombinant expression of human cathelicidin (hCAP18/LL-37) in Pichia pastoris - In-Pyo Hong; Sung-Jae Lee; Yong-Seok Kim; Shin-Geon Choi (Biotechnology Letters, 2006)

UV Spectroscopic Monitoring of Vaporized Monoaromatic Hydrocarbons from Petroleum-Contaminated Soils - Woo Jin Kim; Joo In Lee; Seockhun Lee; Kyu-Hong Ahn; Jae-Woo Park (Environmental Monitoring and Assessment, 2006)

Gamma radiation and hormone treatment as tools to reduce salt stress in rice (Oryza sativa L.) - Myung-Hwa Baek; Byung Yeoup Chung; Jin-Hong Kim; Seung Gon Wi; Jae-Sung Kim; In-Jung Lee (Journal of Plant Biology, 2006)

Comparative analysis of expressed sequence tags (ESTs) of ginseng leaf - Myung Kyum Kim; Bum-Soo Lee; Jun-Gyo In; Hua Sun; Jae-Ho Yoon; Deok-Chun Yang (Plant Cell Reports, 2006)

Lidocaine hydrochloride-sodium bicarbonate as an anesthetic for soft-shelled turtle Pelodiscus sinensis - In-Seok PARK; Sung Hwoan CHO; Jun Wook HUR; Gyeng-Cheol CHOI; Sung-Yong OH; Dong Soo KIM; Jae-Seong LEE (Fisheries Science, 2006)

Comparison and Analysis of the Complete Nucleotide Sequence of Foot-and-Mouth Disease Viruses from Animals in Korea and Other PanAsia Strains - Jae Ku Oem; Kwang Nyeong Lee; In Soo Cho; Soo Jeong Kye; Jong Hyeon Park; Yi Seok Joo (Virus Genes, 2004)

Growth promotion of red pepper plug seedlings and the production of gibberellins by Bacillus cereus, Bacillus macroides and Bacillus pumilus - Gil-Jae Joo; Young-Mog Kim; In-Jung Lee; Kyung-Sik Song; In-Koo Rhee (Biotechnology Letters, 2004)

Gene Cloning, Sequencing, and Expression of an Esterase from Acinetobacter lwoffii I6C-1 - Hye Eun Kim; In Soo Lee; Joo Hwan Kim; Kyu Woong Hahn; Ul Jae Park; Hyon Soo Han; Kyeong Ryang Park (Current Microbiology, 2003)

Modified Magnetic Resonance Image Based Parcellation Method for Cerebral Cortex using Successive Fuzzy Clustering and Boundary Detection - Uicheul Yoon; Jong-Min Lee; Jae-Jin Kim; Sang Min Lee; In Young Kim; Jun Soo Kwon; Sun I. Kim (Annals of Biomedical Engineering, 2003)

Isolation and characterization of a myo-inositol 1-phosphate synthase cDNA from developing sesame (Sesamum indicum L.) seeds: functional and differential expression, and salt-induced transcription during germination - Jae-An Chun; Un-Ho Jin; Jin-Woo Lee; Young-Byung Yi; Nam-In Hyung; Myung-Hwa Kang; Jae-Ho Pyee; Mi Suh; Churl-Whan Kang; Hong-Yeol Seo; Shin-Woo Lee; Chung-Han Chung (Planta, 2003)

Phylogenetic Relationship of Microcystis (Cyanophyceae) Based on Partial 16S rRNA Gene Sequences in Korea - Jong-In Kim; Jong-Hun Lim; Jae-Wan Lee; Hae-Bok Lee (Algae, 2002)

Movement history of the Andong Fault System: Geometric and tectonic approaches - Pom-yong Choi; Seung Ryeol Lee; Hyen -Il Choi; Jae-ha Hwang; Seok-ki Kwon; In-sae Ko; Gi-o An (Geosciences Journal, 2002)

Environmental fate of the triazole fungicide propiconazole in a rice-paddy-soil lysimeter - In Seon Kim; Lee A. Beaudette; Jae Han Shim; Jack T Trevors; Yong Tack Suh (Plant and Soil, 2002)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)

A ncovel angiogenic factor derived from Aloe vera gel: β-sitosterol, a plant sterol - Eun-Joung Moon; You Mie Lee; Ok-Hee Lee; Myoung-Jin Lee; Seung-Ki Lee; Myung-Hee Chung; Young-In Park; Chung-Ki Sung; Jae-Soo Choi; Kyu-Won Kim (Angiogenesis, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)